Prediksi Tingkat Keuntungan Usaha Peternakan Itik Alabio Petelur menggunakan Jaringan Syaraf Tiruan Backpropagation (Kasus di Kabupaten Hulu Sungai Utara Kalimantan Selatan) - Muhammad Ihsan Diputra; Candra Dewi; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Predicting profits in ducks farming business is very hard to do. That's because in alabio duck agribusiness system have subsystems that can effect other subsystems. If the subsystems don't have optimal value it can make a bad impact for profits in business. To overcome this problem, this study using backpropagation artificial neural network to predict profit in alabio duck eggs business. This study using backpropagation algorithm because this algorithm often used for forecasting. The subsystems or input features used in this study are number of adult ducks, shrinkage of duck seed price, total food price, shrinkage of cages price, labor costs, and the cost of vaccines and medicine. The system in this study use net profits of duck eggs business as output. In this study, testing used to get the optimal value for each parameter. The values of each parameters are learning rate 0.8, 17 hidden neuron, MAPE learn threshold 10%, and 90% total data training. The best MAPE for forecasting result is 25,7852%.